2013
DOI: 10.1088/0951-7715/26/10/2851
|View full text |Cite
|
Sign up to set email alerts
|

Shades of hyperbolicity for Hamiltonians

Abstract: Abstract. We prove that a Hamiltonian system H ∈ C 2 (M, R) is globally hyperbolic if any of the following statements holds: H is robustly topologically stable; H is stably shadowable; H is stably expansive; and H has the stable weak specification property. Moreover, we prove that, for a C 2 -generic Hamiltonian H, the union of the partially hyperbolic regular energy hypersurfaces and the closed elliptic orbits, forms a dense subset of M . As a consequence, any robustly transitive regular energy hypersurface o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Similar results are obtained when considering even feeble properties like the weak shadowing and the specification properties. Despite the Hamiltonian nature of the geodesic flow, the arguments in the present paper differ completely from those used in [5] for Hamiltonian systems.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Similar results are obtained when considering even feeble properties like the weak shadowing and the specification properties. Despite the Hamiltonian nature of the geodesic flow, the arguments in the present paper differ completely from those used in [5] for Hamiltonian systems.…”
mentioning
confidence: 81%
“…The case of Hamiltonian systems yields some surprising consequences arising from numerical properties. If we assume C 2 -robustness of shadowing, then the closure of the periodic points is a uniformly hyperbolic set [5]. Thus, due to the general density theorem for Hamiltonians [20], the Hamiltonian is Anosov.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another result which relates C 1 -robust properties with hyperbolicity is the result in [11] which states that C 1 -robustly transitive incompressible flows have dominated splitting. See also the results in [13,14,47] for flows and in [38,40] for diffeomorphisms.…”
Section: Asymptotic) Average Shadowable Admits a Dominated Splitting Onmentioning
confidence: 99%
“…Bessa et al [8] shoed that if a Hamiltonian system is C 2 -robustly expansive then it is Anosov. In [7], Bessa and Rocha showed that a symplectic diffeomorphism is C 1 -robustly expansive then it is Anosov.…”
Section: O M / L O C a T E / C H A O Smentioning
confidence: 99%